التطور الكمي والنوعي للنفايات الصلبة الحضرية في بلدية الوادي وإمكانية تثمينها - العابد, رشيدة; دادن, عبد الغني (جامعة الوادي - University of Eloued, 2017)
يمثل تسيير النفايات الصلبة الحضرية تحديا حقيقيا على المستوى العالمي، الاقليمي، والمحلي نظرا للآثار السلبية الاقتصادية والبيئية الناجمة عنه التي تنذر بعواقب خطيرة إذا لم يتم التعامل معها بصورة سليمة، ولقد نجحت الكثير من الدول المتقدمة في تحويل هذا التحدي الى فرص استثمارية هائلة باستخدام آليات وطرق مختلفة، ومن خلال هذا المقال حاولنا دراسة وتحليل التطور الكمي والنوعي للنفايات الصلبة الحضرية لبلدية الوادي، وامكانية تثمينها The conduct of solid waste urban represents a real challenge at the global and regional and local due to her economics and environmental negative effects which warn the severe consequences if they are not handled properly. The development countries succeeded in transforming this challenge to enormous investment opportunities using various mechanisms and methods. This article try to study and analysis the quantitative and qualitative development of waste in el-oued municipality and possibility of recycling.
The Quantitative and Qualitative development of solid waste urban in El-oued and possibility of recycling
مقال بمجلة الدراسات المالية والمحاسبية . مج 08 ع01. جوان 2017 . جامعة الوادي
Keywords: النفايات الصلبة الحضرية، التسيير، التلوث، التدوير، التسميد، بلدية الوادي; Urban solid waste, management, pollution, recycling, composting, Municipality of eloued